Exploring Elements of Fun to Motivate Heavy Drinking Youth to (re)train Cognition - Wouter Boendermaker (Frontiers Media S.A., 2015)
Background Excessive use of alcohol during adolescence poses a serious health risk. It can lead to cognitive impairment, as well as addictive problems later in life. Recent reviews have concluded that Cognitive Bias Modification (CBM) shows promise as an intervention method in this field. While effective in long time users, most adolescents lack a motivation to train. To improve motivation we have explored several techniques to introduce elements of fun to CBM. Aims First we will discuss a number of steps that can be taken to introduce motivating elements to cognitive training. Then we will present two studies that focused on three approaches to enhance user experience and motivation to train: a serious game, a serious game in a social net-working context and a mobile application. Methods In the Game Study, 77 participants performed either a regular CBM training, aimed at response matching, a gamified version or a placebo-version of that training. The gamified version was presented as a stand-alone game or in the context of a social network. In the Mobile Study, 64 participants completed a different CBM training, aimed at approach bias, either on a computer or on their mobile device. Results Despite heavy drinking among the subjects, no CBM training effects were found in the Game Study. Adding (social) game elements did however increase aspects of the user experience and motivation to train. The mobile training appeared to increase motivation to train in terms how often participants trained, but this effect disappeared after controlling for baseline motivation to train. Conclusions Adding (social) game elements can increase motivation to train, and while the mobile training did not appear to be more motivating, it also did not underperform compared to the regular training in this sample. This warrants more research into motivational elements for CBM training in younger audiences.